Supported noble metal hydride for formate dehydrogenation and preparation method thereof

By wet impregnation and heat treatment on microporous carbon or microporous carbon nitrogen materials, the problem of inactivation of precious metal catalysts at high temperatures is solved, and efficient and stable hydrogen release and large-scale industrial synthesis are achieved.

CN119733550AActive Publication Date: 2025-04-01SHANGHAI JIAOTONG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510049971.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-01
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

Existing precious metal catalysts are prone to inactivate during high-temperature hydrogen release, and large-scale industrial synthesis is difficult to achieve, so they cannot effectively, stably and efficiently release hydrogen.

Method used

Through wet impregnation method and reducing solution heat treatment hydrogenation method, uniform high-temperature stable precious metal hydride nanoparticles are generated on the surface of microporous carbon or microporous carbon nitrogen materials with high specific surface area to prepare a supported precious metal hydride catalyst.

Benefits of technology

It has achieved a supported precious metal hydride catalyst with excellent high-temperature dehydrogenation performance and stable structural and catalytic performance. It can be prepared on a large scale and has important applications in chemical industry, energy and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733550A_ABST
    Figure CN119733550A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of dehydrogenation catalytic materials, and particularly discloses a supported noble metal hydride for formate dehydrogenation and a preparation method thereof. According to the preparation method, microporous carbon or a microporous carbon-nitrogen material is used as a carrier, then noble metal is used as a precursor, a wet impregnation method is utilized to obtain loaded noble metal, and finally, a reducing agent is used for high-temperature treatment to obtain the loaded noble metal hydride. The supported noble metal hydride has the characteristics of simple preparation process, greenness, safety, low cost and good performance, and can meet the requirements of large-scale production. The supported noble metal hydride can be used for efficient and stable formate hydrogen desorption, and has very wide application potential in multiple fields such as energy conversion and storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of dehydrogenation catalytic materials, and in particular relates to a supported noble metal hydride for formate dehydrogenation and a preparation method thereof. Background Art

[0002] In recent years, the production of a variety of value-added fuels or chemicals, including methanol, ethanol, formic acid, etc., by catalytic hydrogenation of CO2 has been widely reported. However, considering the annual CO2 emissions and actual usage, the potential technology of CO2 value-added must provide important chemical intermediates or high-consumption end products, and energy carriers are ideal products. Among several chemicals that can be directly prepared from CO2, formic acid (FA) is widely used in the textile, leather or dye industry and as a cleaning or disinfection solution. More importantly, formic acid can be used as a hydrogen storage molecule and is an ideal hydrogen energy carrier, while playing an emerging role in fuel cell technology and potential biomass upgrading.

[0003] The calorific value of hydrogen is 143KJ / g, which is 3 times that of oil and 4.5 times that of coal. It is an efficient clean energy and is identified as an important energy source in the future. The storage and transportation of hydrogen are the key to the utilization of hydrogen energy. Organic liquid hydrogen storage is favored by researchers as a safe and convenient way. Formic acid has a high hydrogen storage capacity (53g·L -1 ), is an excellent and safe hydrogen carrier that is easy to store and release hydrogen. Therefore, the closed-loop conversion based on carbonates and formic acid / formates to achieve the storage and utilization of hydrogen energy is a three-birds-with-one-stone thing, which can not only alleviate environmental problems, but also reduce the use of fossil energy, providing an ideal carrier for the safe transportation and use of hydrogen energy. The development of suitable catalysts is the key to achieving the goal of efficiently converting CO2 hydrogenation into HCOOH / HCOOX, and then decomposing HCOOH / HCOOX to release hydrogen. Among them, how to stably and efficiently release hydrogen in application scenarios is the top priority.

[0004] Heterogeneous catalysts have received extensive attention in recent years because they are easy to recycle and reuse, more in line with the principles of green chemistry, and have greater economic advantages. Precious metals, especially palladium-based precious metals, are a type of catalyst that has been widely studied and are used in both hydrogenation and dehydrogenation. However, precious metal catalysts are often prone to deactivation during high-temperature dehydrogenation. At present, the research results on improving the stability of precious metal-based dehydrogenation are mainly focused on the structural design of precious metal components. By designing a fine carrier structure to improve the dispersibility of palladium clusters or nanoparticles or filling the catalyst with earth-abundant metal elements to synthesize alloys or core-shell structures of palladium-based bimetallic or multimetallic catalysts, the catalytic activity and stability of precious metals are finally further improved. However, these precise and complex synthesis methods cannot provide large-scale industrial synthesis of gram-level catalysts, and are still insufficient to achieve efficient and stable dehydrogenation effects. The special structure of precious metal hydrides makes them have great application potential in dehydrogenation reactions, but the current synthesis method conditions are relatively complex, difficult to prepare on a large scale, and there are problems such as structural instability in high-temperature liquid environments.

[0005] Based on the above points, the present invention focuses on the structural design of efficient and stable noble metal hydride catalysts, aiming at large-scale preparation of noble metal hydride catalysts supported by microporous carbon with high specific area. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a supported noble metal hydride for formate dehydrogenation and a preparation method thereof, wherein the method generates uniform high-temperature stable noble metal hydride nanoparticles on the surface of a microporous support with a high specific surface area through a simple wet impregnation method and a reducing solution heat treatment hydrogenation method, thereby obtaining a supported noble metal hydride material. The supported noble metal hydride material has a simple synthesis method, mature industrial preparation conditions, and has excellent high-temperature dehydrogenation performance, and can achieve efficient and stable dehydrogenation.

[0007] The specific technical solution adopted by the present invention is as follows:

[0008] In a first aspect, the present invention provides a method for preparing a supported noble metal hydride for dehydrogenation of formate, which specifically comprises the following steps:

[0009] (1) Wet impregnation: The microporous carbon support material is dispersed in water by ultrasound and stirring, and a solution containing noble metal ions is dropped into the water containing the microporous carbon support material, stirred at room temperature, and then dried. The resulting solid sample is a loaded noble metal;

[0010] (2) Thermal reduction hydrogenation treatment: The supported noble metal material is dispersed in a reducing agent solution, heated and stirred, washed and dried to obtain a supported metal hydride.

[0011] Furthermore, in step (1), the microporous carbon carrier is a microporous carbon material or a microporous carbon-nitrogen material synthesized by a preparation method such as a sealed tube ion salt melting method or a template method calcination method, and is preferably a microporous carbon-nitrogen material. The microporous structure rich in microporous nitrogen and carbon is conducive to the uniform distribution of the loaded noble metal hydride, and nitrogen-doped carbon will regulate the energy band structure, change the electronic structure of the noble metal hydride, help the dehydrogenation, and improve the efficiency and sustainability of the dehydrogenation reaction.

[0012] Furthermore, the microporous carbon carrier material has a specific surface area of ​​1400 m 2 / g or more, pore volume greater than 0.6cm 3 / g, the pore size distribution is 0.5-2nm; if it is microporous carbon nitrogen, the nitrogen content is 4-12% (mass fraction).

[0013] Further, in step (1), the noble metal includes but is not limited to one or more of palladium, platinum, ruthenium, rhodium, and iridium; the solution containing the noble metal can be a solution of a palladium precursor (chloropalladic acid, sodium chloropalladate, potassium chlorate, etc.), a platinum precursor (chloroplatinic acid, sodium chloroplatinate, etc.), a ruthenium precursor (ruthenium trichloride, etc.), preferably chloropalladic acid. Among the noble metal hydrides, palladium noble metal has the best dehydrogenation performance.

[0014] Furthermore, in step (2), the reducing agent solution includes but is not limited to one of a formate solution (ammonium formate, potassium formate, sodium formate, etc.), a hydrazine hydrate solution, and a sodium borohydride solution, preferably ammonium formate. Among the reducing agent solutions, ammonium formate has the best hydrogenation ability among formates and is safer than hydrazine hydrate and sodium borohydride.

[0015] Furthermore, in step (2), the concentration of the reducing agent solution is 0.5-10 M, the heating temperature is 40-120° C., and the heating time is 30-180 min.

[0016] In a second aspect, the present invention provides a supported noble metal hydride for formate dehydrogenation prepared by the above preparation method.

[0017] Furthermore, in the supported noble metal hydride, the mass percentage of the noble metal element is 0.0001-60wt%

[0018] The present invention has the following beneficial effects:

[0019] 1. The present invention uses microporous carbon or microporous carbon-nitrogen material as a carrier, and synthesizes supported precious metal hydrides by wet impregnation method and reduction solution heat treatment method. This method has the advantages of simple process, green safety, easy control, etc., and can realize large-scale production and preparation.

[0020] 2. The supported noble metal hydride synthesized by the present invention has the characteristics of excellent high-temperature dehydrogenation performance, stable structure and catalytic performance, etc.

[0021] 3. The efficient and stable dehydrogenation precious metal hydride catalyst developed by the present invention will not only have important applications in the fields of chemical industry and energy, but will also provide a new perspective for the research on organic liquid hydrogen energy storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a diagram showing the nitrogen absorption and desorption of the supported palladium hydride material of Example 1.

[0023] Figure 2 TEM transmission electron microscope image and HAADF image of the supported palladium hydride material in Example 1.

[0024] Figure 3 This is the X-ray diffraction pattern of the supported palladium hydride material of Example 1.

[0025] Figure 4 This is a high-temperature dehydrogenation performance diagram of the supported palladium hydride material of Example 1, the material of Comparative Example 1, and the material of Comparative Example 2 (reaction conditions: 2M ammonium formate, n(HCOO-) / n(Pd)=2128, 60°C). DETAILED DESCRIPTION

[0026] The present invention loads the noble metal source onto the microporous carbon carrier material by wet impregnation, and then heat-treats the obtained supported noble metal material using a reducing solution to obtain a supported metal hydride material. The specific preparation method is as follows:

[0027] (1) Wet impregnation: The microporous carbon support material is dispersed in water by ultrasound and stirring, and a solution containing noble metal ions is dropped into the water containing the microporous carbon support material, stirred at room temperature, and then dried. The resulting solid sample is a loaded noble metal. Wherein:

[0028] The microporous carbon carrier material is a high specific area microporous carbon material or a microporous carbon nitrogen material; microporous carbon and microporous carbon nitrogen represent a class of carbon materials or nitrogen-doped carbon materials with a microporous structure prepared by any method. The material can be purchased as a commercial product or prepared by itself, and needs to meet the following requirements:

[0029] The specific surface area of ​​the microporous carbon carrier material is 1400m 2 / g or more, pore volume greater than 0.6cm 3 / g, pore size distribution is 0.5-2nm;

[0030] The microporous carbon material can specifically be a molecular sieve, microporous nanocarbon fiber, microporous nanocarbon sphere, etc.

[0031] The nitrogen content of the microporous carbon-nitrogen material is 4%-12%. The preparation method of the material is exemplified as follows: the material is prepared by a sealed tube ion salt melting method, using a zinc ion salt (as a central ion to induce cyano polymerization of a carbon-nitrogen source, and then bond to finally generate a carbon-nitrogen material) and a carbon-nitrogen source (including but not limited to one or more of 2,6-dicyanopyridine, terephthalonitrile, 1,3,5-triphenylnitrile, 4,4'-biphenyl dinitrile, 2,5-dicyanothiophene, etc.), and then sealed tube calcined (800-1200°C), washed and dried to obtain the material.

[0032] The precious metal includes but is not limited to one or more of palladium, platinum, ruthenium, rhodium, and iridium; the solution containing the precious metal can be a solution of a palladium precursor (chloropalladic acid, sodium chloropalladate, potassium chlorate, etc.), a platinum precursor (chloroplatinic acid, sodium chloroplatinate, etc.), a ruthenium precursor (ruthenium trichloride, etc.), or the like.

[0033] (2) Thermal reduction treatment: Disperse the supported precious metal material in a reducing agent solution, heat and stir, wash and dry to obtain a supported metal hydride. Wherein:

[0034] The reducing agent solution includes but is not limited to one of a formate solution (ammonium formate, potassium formate, sodium formate, etc.), a hydrazine hydrate solution, and a sodium borohydride solution; the reducing agent solution concentration is 0.5-10M; the heating temperature is 40-120°C, and the heating time is 30-180min.

[0035] The difficulty of the present invention lies in synthesizing stable and efficient hydride materials. The existing impregnation reduction can only prepare conventional supported metals, and this type of catalyst shows poor stability during the dehydrogenation process. In the supported metal hydride synthesized by the present invention, the high specific surface area microporous carbon carrier material can provide a larger contact area, and is more conducive to the formation of small-sized metal nanoparticles, and is more conducive to adjusting the electronic structure of the surface of the nanoparticles to achieve efficient dehydrogenation efficiency; and the metal loaded in the microporous material can also achieve a special confinement effect so that the small-sized nanoparticles will not aggregate and become larger in the high-temperature dehydrogenation environment, and the activity will not decrease, thereby achieving excellent structural stability.

[0036] The factors affecting the product quality of the present invention mainly include carrier materials and thermal reduction hydrogenation reduction treatment. The key is that the carrier must have a microporous structure and perform relevant parameter control, wherein the specific surface area of ​​the carrier will affect the contact between the catalyst and the reaction solution, too low will affect the dehydrogenation rate, the size of the pore size and the nitrogen content will affect the dispersion of the catalyst metal on the carrier, small pore size and high nitrogen content are the key to forming uniform dispersion of small particles, too large pore size cannot be confined to reduce the catalytic activity, too low nitrogen content will affect the combination of metal and carrier and then affect the stability of the catalyst, and the upper limit of nitrogen content is the synthesis upper limit. In terms of thermal reduction hydrogenation treatment, the reducing solution should have a suitable hydrogenation capacity (too violent hydrogenation reducing agent will destroy the small-sized metal load, causing the hydrogenation metal particles to aggregate and become larger, and too violent hydrogenation reducing agent has a safety risk; therefore, in addition to the type of reducing agent, reducing agent concentration, reduction heat temperature, and safety are all factors to be considered).

[0037] The following is a specific example of catalyst preparation according to the above method, which is used to further illustrate the present invention. The microporous carbon-nitrogen materials used in the following examples are all prepared by using zinc chloride and 2,6-dicyanopyridine, calcining in a sealed tube, washing and drying.

[0038] Example 1

[0039] 5 g of microporous carbon nitride material was dispersed in water by ultrasound and stirring, and a chloropalladic acid solution containing 250 mg of palladium was dropped into the water containing the microporous carbon nitride material and stirred at room temperature, followed by reduction. The obtained product was heat treated at 80°C for 30 min using 2M ammonium formate to obtain a supported palladium hydride material.

[0040] Example 2

[0041] 5 g of microporous carbon nitride material was dispersed in water by ultrasound and stirring, and a chloroplatinic acid solution containing 250 mg of platinum was dropped into the water containing the microporous carbon nitride material and stirred at room temperature, followed by reduction. The obtained product was heat treated at 80°C for 30 min using 2M ammonium formate to obtain a supported platinum hydrogenated material.

[0042] Example 3

[0043] 5 g of microporous carbon nitride material was dispersed in water by ultrasound and stirring, and a ruthenium trichloride solution containing 250 mg of ruthenium was dropped into the water containing the microporous carbon nitride material and stirred at room temperature. Then, the reduced product was heat treated at 80°C for 30 min using 2M ammonium formate to obtain a supported ruthenium hydrogenated material.

[0044] Example 4

[0045] 5 g of microporous carbon molecular sieve material was dispersed in water by ultrasound and stirring, and a chloropalladic acid solution containing 250 mg of palladium was dropped into the water containing the microporous carbon molecular sieve and stirred at room temperature, followed by reduction. The obtained product was heat-treated at 80°C for 30 min using 2M ammonium formate to obtain a supported palladium hydride material.

[0046] Example 5

[0047] 5 g of microporous carbon nitride material was dispersed in water by ultrasound and stirring, and a chloropalladic acid solution containing 250 mg of palladium was dropped into the water containing the microporous carbon nitride material and stirred at room temperature, followed by reduction. The obtained product was heat treated at 80°C for 30 min using 2M sodium formate to obtain a supported palladium hydride material.

[0048] Example 6

[0049] 5 g of microporous carbon nitride material was dispersed in water by ultrasound and stirring, and a chloropalladic acid solution containing 250 mg of palladium was dropped into the water containing the microporous carbon nitride material and stirred at room temperature, followed by reduction. The obtained product was heat treated at 80°C for 30 min using 2M potassium formate to obtain a supported palladium hydride material.

[0050] Example 7

[0051] 5 g of microporous carbon nitride material was dispersed in water by ultrasound and stirring, and a chloropalladic acid solution containing 250 mg of palladium was dropped into the water containing the microporous carbon nitride material and stirred at room temperature, followed by reduction. The obtained product was heat-treated at 80°C for 30 min using 2M lithium formate to obtain a supported palladium hydride material.

[0052] Example 8

[0053] 5 g of microporous carbon nitride material was dispersed in water by ultrasound and stirring, and a chloropalladic acid solution containing 250 mg of palladium was dropped into the water containing the microporous carbon nitride material and stirred at room temperature, followed by reduction. The obtained product was heat treated at 80°C for 30 min using 2M cesium formate to obtain a supported palladium hydride material.

[0054] Example 9

[0055] 5 g of microporous carbon nitride material was dispersed in water by ultrasound and stirring, and a chloropalladic acid solution containing 250 mg of palladium was dropped into the water containing the microporous carbon nitride material and stirred at room temperature, followed by reduction. The obtained product was heat treated at 80°C for 30 min using 2M formic acid to obtain a supported palladium hydride material.

[0056] Example 10

[0057] 5 g of microporous carbon nitride material was dispersed in water by ultrasound and stirring, and a chloropalladic acid solution containing 250 mg of palladium was dropped into the water containing the microporous carbon nitride material and stirred at room temperature. Then, the reduced product was heat treated at 80°C for 30 min using 2M sodium borohydride to obtain a supported palladium hydride material.

[0058] Embodiment 11

[0059] 5 g of microporous carbon nitride material was dispersed in water by ultrasound and stirring, and a chloropalladic acid solution containing 250 mg of palladium was dropped into the water containing the microporous carbon nitride material and stirred at room temperature, followed by reduction. The obtained product was heat treated at 80°C for 30 min using 2M hydrazine hydrate to obtain a supported palladium hydride material.

[0060] Example 12

[0061] 5 g of microporous carbon nitride material was dispersed in water by ultrasound and stirring, and a chloropalladic acid solution containing 2.5 mg of palladium was dropped into the water containing the microporous carbon nitride material and stirred at room temperature, followed by reduction. The obtained product was heat treated at 80°C for 30 min using 2M ammonium formate to obtain a supported palladium hydride material.

[0062] Example 13

[0063] 5 g of microporous carbon nitride material was dispersed in water by ultrasound and stirring, and a chloropalladic acid solution containing 25 mg of palladium was dropped into the water containing the microporous carbon nitride material and stirred at room temperature, followed by reduction. The obtained product was heat treated at 80°C for 30 min using 2M ammonium formate to obtain a supported palladium hydride material.

[0064] Embodiment 14

[0065] 5 g of microporous carbon nitride material was dispersed in water by ultrasound and stirring, and a chloropalladic acid solution containing 2.5 g of palladium was dropped into the water containing the microporous carbon nitride material and stirred at room temperature, followed by reduction. The obtained product was heat treated at 80°C for 30 min using 2M ammonium formate to obtain a supported palladium hydride material.

[0066] Embodiment 15

[0067] 5 g of microporous carbon nitride material was dispersed in water by ultrasound and stirring, and a chloropalladic acid solution containing 250 mg of palladium was dropped into the water containing the microporous carbon nitride material and stirred at room temperature, followed by reduction. The obtained product was heat treated at 80°C for 30 min using 0.5 M ammonium formate to obtain a supported palladium hydride material.

[0068] Example 16

[0069] 5 g of microporous carbon nitride material was dispersed in water by ultrasound and stirring, and a chloropalladic acid solution containing 250 mg of palladium was dropped into the water containing the microporous carbon nitride material and stirred at room temperature. Then, the reduced product was heat treated at 80°C for 30 min using 10 M ammonium formate to obtain a supported palladium hydride material.

[0070] Embodiment 17

[0071] 5 g of microporous carbon nitride material was dispersed in water by ultrasound and stirring, and a chloropalladic acid solution containing 250 mg of palladium was dropped into the water containing the microporous carbon nitride material and stirred at room temperature, followed by reduction. The obtained product was heat treated at 40°C for 30 min using 2 M ammonium formate to obtain a supported palladium hydride material.

[0072] Embodiment 18

[0073] 5 g of microporous carbon nitride material was dispersed in water by ultrasound and stirring, and a chloropalladic acid solution containing 250 mg of palladium was dropped into the water containing the microporous carbon nitride material and stirred at room temperature, followed by reduction. The obtained product was heat treated at 120°C for 30 min using 2M ammonium formate to obtain a supported palladium hydride material.

[0074] Embodiment 19

[0075] 5 g of microporous carbon nitride material was dispersed in water by ultrasound and stirring, and a chloropalladic acid solution containing 250 mg of palladium was dropped into the water containing the microporous carbon nitride material and stirred at room temperature. Then, the reduced product was heat treated at 80°C for 180 min using 2 M ammonium formate to obtain a supported palladium hydride material.

[0076] Comparative Example 1: Preparation of palladium-supported commercial carbon

[0077] This comparative example uses a carbon carrier that is currently widely studied. The carbon powder purchased from the chemical platform is not subjected to other treatment. 5g of carbon powder is dispersed in water by ultrasound and stirring. A chloropalladic acid solution containing 250mg of palladium is dripped into the water containing the microporous carrier material and stirred at room temperature. The product is then reduced and washed and dried to obtain a palladium-based heterogeneous material. The obtained material is compared with the material in Example 1 for dehydrogenation performance. It is found that the high-temperature dehydrogenation performance stability of this comparative example is very poor, which is significantly worse than that of Example 1 ( Figure 4 ).

[0078] Comparative Example 2

[0079] The same as Example 1, except that the carrier is a non-microporous mesoporous carbon-nitrogen material. The dehydrogenation performance of the obtained catalyst material is compared with that of Example 1. It is found that the high-temperature dehydrogenation performance of this comparative example is significantly worse than that of Example 1 ( Figure 4 ).

[0080] The supported noble metal hydride materials prepared in Examples 1 to 19 all have the advantages of uniform distribution and stable structure, and can achieve stable and efficient high-temperature dehydrogenation. The following are the results of observation and evaluation of the supported noble metal hydride materials obtained in Example 1.

[0081] Figure 1 The nitrogen absorption and desorption diagram of the supported palladium hydride material of Example 1 shows that the prepared supported palladium hydride material has a microporous high specific surface area (2135.5m 2 / g).

[0082] Figure 2 This is a transmission electron microscope image of the supported palladium hydride material of Example 1. It can be seen that a uniformly distributed supported palladium hydride material was prepared.

[0083] Figure 3 This is the X-ray diffraction diagram of the supported palladium hydride material of Example 1. It can be seen that obvious characteristic diffraction peaks of palladium hydride appear, proving that palladium hydride is successfully prepared.

[0084] Figure 4 The high temperature dehydrogenation performance diagram of the supported palladium hydride material of Example 1 (blue), Comparative Example 1 (gray) and Comparative Example 2 (black) (reaction conditions: 2M ammonium formate, n(HCOO-) / n(Pd)=2128, 60°C). It can be seen that the supported palladium hydride material of Example 1 can continuously decompose formate to produce hydrogen, while the dehydrogenation rates of Comparative Examples 1 and 2 drop sharply and the reaction duration is short, which shows that the supported noble metal hydride material prepared by the present invention can dehydrogenate formate at high temperature, and the dehydrogenation is efficient and stable.

[0085] This specific implementation is only an explanation of the present invention, not a limitation of the present invention. Any changes made by those skilled in the art after reading the specification of the present invention will be protected by the patent law as long as they are within the scope of the claims of the present invention.

Claims

1. A method for preparing a supported noble metal hydride for formate dehydrogenation, characterized in that: The following steps are involved: (1) Wet impregnation: The microporous carbon support material is dispersed in water by ultrasound and stirring, and a solution containing noble metal ions is dropped into the water containing the microporous carbon support material, stirred at room temperature, and then dried. The resulting solid sample is a loaded noble metal; (2) Thermal reduction treatment: The supported noble metal material is dispersed in a reducing agent solution, heated and stirred, washed and dried to obtain a supported metal hydride.

2. The method for preparing a supported noble metal hydride for formate dehydrogenation according to claim 1, characterized in that: In step (1), the microporous carbon carrier material is a microporous carbon material or a microporous carbon-nitrogen material.

3. The method for preparing a supported noble metal hydride for formate dehydrogenation according to claim 2, characterized in that: In step (1), the specific surface area of ​​the microporous carbon carrier material is 1400m 2 / g or more, pore volume greater than 0.6cm 3 / g, the pore size distribution is 0.5-2nm; the nitrogen content of the microporous carbon nitrogen is 4-12%.

4. The method for preparing a supported noble metal hydride for formate dehydrogenation according to claim 1, characterized in that: In step (1), the noble metal is one or more of palladium, platinum, ruthenium, rhodium and iridium.

5. The method for preparing a supported noble metal hydride for formate dehydrogenation according to claim 1, characterized in that: In step (2), the reducing agent solution is one of a formate solution, a hydrazine hydrate solution, and a sodium borohydride solution.

6. The method for preparing a supported noble metal hydride for formate dehydrogenation according to claim 1, characterized in that: In step (2), the concentration of the reducing agent solution is 0.5-10M, the heating temperature is 40-120°C, and the heating time is 30-180min.

7. A supported noble metal hydride for formate dehydrogenation obtained by the preparation method according to any one of claims 1 to 6.

8. The supported noble metal hydride for formate dehydrogenation according to claim 7, characterized in that: In the supported noble metal hydride, the mass percentage of the noble metal element is 0.0001-60wt%.

Citation Information

Patent Citations

  • Catalyst for synthesizing methyl formate by formylating methyl nitrite, preparation method and application of catalyst

    CN103894232A

  • Method for catalyzing hydrogen production from formic acid

    CN108675262A

  • Catalyst for catalyzing oxidative dehydrogenation and hydrogenation reaction of organic compound and application thereof

    CN113058644A

  • Pd hydride catalyst for direct alcohol fuel cell and preparation method of Pd hydride catalyst

    CN115000424A

  • DD65561A